ATTITUDES OF THE CONSUMERS REGARDING THEIR PERSONAL DATA: WHAT HAS CHANGED UNDER THE RECENT YEARS? - Dugulan Diana; Acatrinei Carmen; Orzan Mihai; Veghes Calin (Annals of the University of Oradea: Economic Science, 2012)
The historical roots of the debates regarding the privacy are to be found in the conclusion issued, at the end of the 19th century, by the Pacific Railway Commission (1887), on the essential, for the citizenâ€™s peace and happiness, â€œright of personal securityâ€, and the individualâ€™s â€œright to be left aloneâ€, approached and explained by Louis Brandies (1890). Since then, many definitions have been given aiming to explain the content of privacy from different angles but all these attempts were rather difficult and succeeded to clarify things only partially, due to the various perspectives considered. The information age has made even more difficult not only the definition of privacy, but its defense in front of the many invading ways based mainly on the internet employment. From a marketing perspective, the definition of privacy should focus on the personal data regarding the consumers, the extent to what this data is communicated to or is collected by others, and the subsequent data treatment, in terms of the processing and employment, by the entities managing this information. In this context, the privacy should be considered in connection with its particular area of application â€“ the consumerâ€™s private space â€“ described by the amount of information regarding the demographics, psychographics and behavioral characteristics of the individuals, and the rights they should have to disclose or not their personal data, and to have this data protected through the appropriate laws and means. The paper aims to assess, in a longitudinal approach, the attitudes of the consumers, and the specific differences, regarding their personal data in terms of their disclosure, the previous consent the consumers should express to the companies or public entities collecting them, and capturing, processing, and further employment by the companies, based on the primary data collected in two surveys conducted in January 2010 and 2012.